Geochemical and Geological Characterization of Upper Permian Linghao Formation Shale in Nanpanjiang Basin, SW China - Gu, Yifan; Cai, Guangyin; Hu, Dongfeng; Wei, Zhihong; Liu, Ruobing; Han, Jing; Fan, Zhiwei; Hao, Jingyu; Jiang, Yuqiang (Frontiers in Earth Science, 2022)
The Upper Permian Linghao Formation shale is the most potential shale gas exploration target in Nanpanjiang Basin. In this study, X-ray diffraction, field emission scanning electron microscopy, CH4 isothermal adsorption, and nuclear magnetic resonance cryoporometry are intergrated to reveal comprehensive characterization of Linghao Formation shale collected from a well in Nanpanjiang Basin. Results indicate that organic-rich shales developed in the Ling 1 member and the lower part of Ling 3 member. The organic-rich shales are predominantly characterized by kerogen type I, with a relatively highly mature to overmature status. The Ling 1 organic-rich shale mainly consists of mixed shale lithofacies, and the organic-rich shale in the lower part of Ling 3 is mainly composed of argillaceous shale. The pore volume in Ling 1 organic-rich shale is mainly contributed by 3- to 6-nm and 8- to 11-nm organic pores. The pore volume of Ling 3 organic-rich shale is mainly contributed by 2- to 3-nm and 4- to 11-nm organic pores. The organic pores between 3 and 10 nm also have a small contribution to the pore volume. The absolute adsorption gas content of Ling 1 and Ling 3 organic-rich shale is 1.21 m3/t and 1.64 m3/t, respectively. The absolute adsorption gas content of Ling 1 and Ling 3 organic-rich shale exceeds the minimum standard for commercial shale gas development in China (1.0 m3/t). According to the adsorption gas ratio of 50%, the total gas content of Ling 1 and Ling 3 organic-rich shale can reach 3.28 m3/t and 2.28 m3/t, respectively. It is suggested that the Upper Permian Linghao Formation shale in the Nanpanjiang Basin has a significant potential for shale gas exploration.